2016
DOI: 10.1104/pp.15.01530
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Is a Critical Regulator of Salt Stress Responses in Rice

Abstract: (A.S.).SUMO (Small Ubiquitin-like Modifier) conjugation onto target proteins has emerged as a very influential class of protein modification systems. SUMO1/2 double mutant plants are nonviable, underlining the importance of SUMO conjugation to plant survival. Once covalently bound, SUMO can alter a conjugated protein's stability and/or function. SUMO conjugation is a highly dynamic process that can be rapidly reversed by the action of SUMO proteases. The balance between the conjugated/ deconjugated forms is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 58 publications
(74 reference statements)
3
64
0
Order By: Relevance
“…Previously we revealed in rice the SUMO protease gene family and showed that OsOTS1 has a key role in tolerance to high salinity (Srivastava et al ., ). Here, we report that drought stress and ABA stimulates the degradation of OsOTS1 protein.…”
Section: Introductionmentioning
confidence: 97%
“…Previously we revealed in rice the SUMO protease gene family and showed that OsOTS1 has a key role in tolerance to high salinity (Srivastava et al ., ). Here, we report that drought stress and ABA stimulates the degradation of OsOTS1 protein.…”
Section: Introductionmentioning
confidence: 97%
“…The SUMO E3 ligase OsSIZ1 regulates phosphate‐ and nitrogen‐dependent responses, spikelet fertility, and plant development in rice (Thangasamy et al ; Wang et al , ). Moreover, the OsOTS1 SUMO protease positively regulates salt stress responses in rice (Srivastava et al ). Mutations in an Arabidopsis SUMO E3 ligase, AtSIZ1 , increase salicylic acid (SA) levels, resulting in reduced plant stature, constitutively activated immune responses, and early flowering (Lee et al ; Jin et al ; Miura et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Rice siz1 alleles that attenuate SUMOylation have a smaller stature with a reduced root system, greater tillering, and reduced fecundity (Thangasamy et al, 2011) and accumulate higher levels of nitrogen and phosphorous, possibly due to the altered expression of genes involved in nutrient uptake (Wang et al, 2015). Conversely, OTS1 overexpression rendered rice resistant to high salt, whereas RNA interference-mediated silencing enhanced salt sensitivity (Srivastava et al, 2016). In addition, significant differences between the monocot and dicot SUMO systems have been observed.…”
mentioning
confidence: 99%